Potentials and Integrated Suitability Pre-assessment of Wastewater Treatment Plants as Local Energy Cells - Neugebauer, Georg; Lichtenwoehrer, Peter; Huber, Franz; Stoeglehner, Gernot; Kretschmer, Florian (Frontiers in Environmental Science, 2022)
In 2018 the European Union has recognized wastewater as a renewable energy source, particularly due to its thermal energy content. To create and further develop knowledge on the possible role that wastewater could play in the energy transition, this article pursues two objectives: 1) it presents an overview on the electric and thermal energy potentials available at the wastewater treatment plants (WWTPs) in the Central European area also taking their spatial context to adjacent settlement structures into account. 2) It introduces a small number of easy to apply criteria to (pre-)assess the suitability of WWTPs for being integrated into local energy (heat) supply concepts from an integrated perspective (considering energetic, spatial and environmental aspects). The investigations address the energy generation potentials of 3,315 WWTPs (with a treatment capacity of at least 5,000 population equivalents) in the area under survey. Analysis reveal, that notable amounts of heat ranging to almost 26 TWh/a are available. Their exploitation appears very promising, as investigations also show, that about 73% of the considered WWTPs are situated near or even within existing settlement structures implying very advantageous heat supply distances. Following the estimation of energy potentials, which is made available in the supplementary material, the presented suitability criteria can then be used to identify the most promising WWTPs in a specific regional/local context, in the investigated Central European area and beyond.